PELAKSANAAN SUPERVISI KLINIS KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALITAS GURU - SALMA SALMA (ACADEMIA: Jurnal Inovasi Riset Akademik, 2022)
This study aims to determine the clinical supervision program, the stages of implementing clinical supervision, teachers' perceptions of clinical supervision and the supporting factors and obstacles to the implementation of clinical supervision. The method used in this research is qualitative. Data collection techniques are: observation, interviews and documentation studies. The research subjects were: principals, school supervisors, and teachers. The results of the research are: (1) the clinical supervision program at MTsN 11 Bireuen is structured based on problems that arise and requests from the teacher, the program is made when the teacher asks for clinical supervision. (2) The implementation of clinical supervision to improve the professional competence of teachers at MTsN 11 Bireuen is carried out in several stages. The first stage is the teacher who feels that he has difficulty going to the supervisor to ask for supervision. In the second stage, the supervisor determines the schedule to develop instruments and techniques for carrying out observations, as well as aids in carrying out observations. The third stage is feedback, the supervisor again gives encouragement and motivates the teacher to continue clinical supervision at the next opportunity; and (3) The existence of a high willingness from teachers who have problems in the teaching and learning process is a supporting factor for the implementation of clinical supervision. ABSTRAKPenelitian ini bertujuan untuk mengetahui program supervisi klinis, tahapan-tahapan pelaksanaan supervisi klinis, persepsi guru terhadap supervisi klinis dan faktor pendukung serta penghambat pelaksanaan supervisi klinis. Metode yang digunakan dalam penelitian adalah kualitatif. Teknik pengumpulan data adalah: observasi, wawancara dan studi dokumentasi. Subjek penelitian adalah: kepala sekolah, pengawas sekolah, dan guru. Hasil penelitian adalah: (1) program supervisi klinis di MTsN 11 Bireuen disusun berdasarkan permasalahan yang timbul dan permintaan dari guru, program dibuat pada saat guru meminta untuk disupervisi klinis. (2) Pelaksanaan supervisi klinis untuk meningkatkan kompetensi profesional guru di MTsN 11 Bireuen dilakukan dengan beberapa tahap. Tahapan pertama guru yang merasa punya kesulitan mendatangi supervisor untuk meminta dilakukan supervisi. Tahapan kedua supervisor menentukan jadwal sampai dengan menyusun instrument dan teknik pelaksanaan observasi, serta alat bantu dalam melaksanakan observasi. Tahap ketiga umpan balik, supervisor kembali memberikan semangat dan memotivasi guru untuk melanjutkan supervisi klinis pada kesempatan berikutnya; dan (3) Adanya kemauan yang tinggi dari guru yang bermasalah dalam proses belajar mengajar merupakan faktor pendukung pelaksanaan supervisi klinis.